1980
DOI: 10.1901/jaba.1980.13-595
|View full text |Cite
|
Sign up to set email alerts
|

Response Deprivation and Reinforcement in Applied Settings: A Preliminary Analysis

Abstract: First-grade children engaged in seatwork behaviors under reinforcement schedules established according to the Premack Principle and the Response Deprivation Hypothesis. Across two experiments, schedules were presented to the children in a counter-balanced fashion which fulfilled the conditions of one, both, or neither of the hypotheses. Duration of on-task math and coloring in Experiment 1 and on-task math and reading in Experiment 2 were the dependent variables. A modified ABA-type withdrawal design, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 25 publications
4
30
1
Order By: Relevance
“…In the case of reinforcement, one must be careful not to set the I/C ratio too high. For example, one of the clients Konarski et al (1980) This ratio correctly predicted the resulting increase in instrumental reading. Konarski et al (1980) chose the 3:2 ratio not only because it would result in an increase in behavior but also because it was practical.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…In the case of reinforcement, one must be careful not to set the I/C ratio too high. For example, one of the clients Konarski et al (1980) This ratio correctly predicted the resulting increase in instrumental reading. Konarski et al (1980) chose the 3:2 ratio not only because it would result in an increase in behavior but also because it was practical.…”
mentioning
confidence: 89%
“…For example, one of the clients Konarski et al (1980) This ratio correctly predicted the resulting increase in instrumental reading. Konarski et al (1980) chose the 3:2 ratio not only because it would result in an increase in behavior but also because it was practical. Three minutes of reading is more than what Sam did during baseline, but is feasible and would result in Sam accessing the reinforcing contingent activity up to four times within each 20 min session.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…In Konarski, Johnson, Crowell, and Whitman (1980) demonstrated that contingent access to a high-probability response (coloring) produced increases in a lowprobability response (completing math problems) only when the reinforcement schedule resulted in the restriction of coloring below its baseline rate. That is, when completion of more math problems than in baseline resulted in access to less coloring than in baseline, time spent on math increased.…”
Section: Economicsmentioning
confidence: 99%
“…Following several demonstrations of disequilibrium (also called response deprivation) schedules in laboratory settings (see Allison, 1993, for a review), Konarski and colleagues (Konarski, Johnson, Crowell, & Whitman, 1980;Konarski, Crowell, & Duggan, 1985) conducted a series of studies using academic or classroom activities, also the focus of the present study. Konarski et al (1980) conducted two experiments with typical first graders using coloring and math problems, and reading and coloring tasks, as the pairs of tasks/responses for which disequilibrium schedules were calculated and implemented.…”
Section: Introductionmentioning
confidence: 99%